Efficiency and productivity growth : modelling in the financial services industry - Pasiouras, Fotios (Chichester, West Sussex : John Wiley & Sons, 2013)
An authoritative introduction to efficiency and productivity analysis with applications in both the banking and finance industry.
Includes bibliographical references (pages 265-266) and index.
oif 24/06/15
Loan
Keywords: Banks and banking -- Econometric models; Financial services industry -- Econometric models